Pemberdayaan Kapasitas Masyarakat melalui Edukasi, Kesehatan, dan Ekonomi Kreatif di Desa Bunter - Mohamad Fazar Fadilah; Aditia Ramadhan; Azima Muhammad Ilham; Azmi Nur Izza; Imran Arrofi Saefulloh; Nita Hasna Aulia; Silvi Fauziah; Ahsyanul Fauziah; Dimas Rizkika Pratama; Amelia Agustin; Evita Putri Fauziyah; Arini Hikmati Miladia; Nabila Putri Sutiani (Universitas Perjuangan Tasikmalaya, 2026)
This service-learning (KKN-PPM) in Bunter Village, Ciamis focused on strengthening community capacity through interventions in education, health, MSME development, environment, digital literacy, and disaster preparedness using participatory approaches (observation, FGDs, and problem–potential mapping) targeting students, women groups, farmers, MSMEs, and village officials. Core programs included literacy corner and Language Club, public speaking training, “Young Pharmacist,” glucose and blood pressure screening, group exercise and parenting, Canva and Microsoft Office training, MSME workshop (packaging–branding–distribution), waste education and biopores, and disaster seminars and simulations. Results indicate improvements in students’ reading interest and confidence, health awareness, basic digital skills, MSME marketing readiness, environmental cleanliness and water conservation, and disaster preparedness. University–village–community collaboration delivered tangible benefits and student learning outcomes. Recommendations include institutionalizing programs in village agendas, post-KKN mentoring, stronger MSME digital marketing and financing access, expanded environmental actions, a village contingency plan, and exploration of organic agriculture and local value-added products.